Metal complex modified azo polymers for multilevel organic memories. Issue 17 (2nd April 2015) - Ma, Yong; Chen, Hong-Xia; Zhou, Feng; Li, Hua; Dong, Huilong; Li, You-Yong; Hu, Zhi-Jun; Xu, Qing-Feng; Lu, Jian-Mei
Abstract : Our approach enables modulating energy levels of azo polymers by varying the coordination metal ions. The ability to tune the bandgap energy of azo polymers provides an opportunity to develop new materials for high density data storage. Abstract : Multilevel organic memories have attracted considerable interest due to their high capacity of data storage. Despite advances, the search for multilevel memory materials still remains a formidable challenge. Herein, we present a rational design and synthesis of a class of polymers containing an azobenzene-pyridine group (PAzo-py) and its derivatives, for multilevel organic memory storage. In this design, a metal complex (M(Phen)Cl2, M = Cu, Pd) is employed to modify the HOMO–LUMO energy levels of azo polymers, thereby converting the memory state from binary to ternary. More importantly, this approach enables modulating the energy levels of azo polymers by varying the coordination metal ions. This makes the achievement of high performance multilevel memories possible. The ability to tune the bandgap energy of azo polymers provides new exciting opportunities to develop new materials for high-density data storage.